Indonesian Language and Culture as Pillars of National Identity in the Digital Education Era - Idawati, Idawati; Febriyanti, Febriyanti (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aimed to investigate the influence of Indonesian language usage, cultural values preservation, and digital education engagement on the formation of national identity among Indonesian students in the digital era. The research addressed the urgent question of how educational practices rooted in language and culture can support national unity amidst rapid technological transformation. Method: A quantitative approach utilizing Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4 was conducted. Data were collected from 350 students across diverse educational institutions using a structured questionnaire with a 5-point Likert scale to measure Indonesian Language Usage (ILU), Cultural Values Preservation (CVP), Digital Education Engagement (DEE), and National Identity (NI). Reliability and validity of constructs were established, and the structural model was evaluated for explanatory power. Results: Measurement model analysis indicated excellent reliability (Cronbach’s alpha 0.88–0.92) and validity (AVE > 0.68). The structural model confirmed that ILU (β = 0.342; p < 0.001), CVP (β = 0.385; p < 0.001), and DEE (β = 0.298; p < 0.001) each contributed significantly and positively to national identity, collectively explaining 67.2% of its variance (R² = 0.672). Novelty: The study provides empirical evidence using advanced SEM-PLS analysis to demonstrate that cultural values have the strongest effect on national identity, followed by language and digital engagement. This highlights the essential role of integrating cultural and linguistic components into digital education design, offering a strategic framework for sustaining Indonesia’s unity in the digital age.